Factors affecting the shariah index in Malaysia / Norfarhana Azeruddin - Azeruddin, Norfarhana (Faculty of Business and Management, 2011)
The focus of this study is to investigate on the factor that effect the shariah index in Malaysia. The researcher focuses on interest rate, currencies and inflation rate. This study will focus on the data collection in the data stream related to the Macro economies information in Malaysia for the past 5year’s period range from November 2006 to August 2010. These studies will only covered nonfinancial listed public companies on The Bursa Malaysia which have been selected as Sharia Compliance Index by using systematic sampling. The objectives of this study is to provide a relevant information and important implication for public policymakers, financial managers and investors on how common stock returns react to factor that’s that will be affect to Shariah Compliance Index besides enhances the demand of the stock. The shariah compliance price will use as a dependent variable. While Based Lending Rate (BLR), USD Exchange Rate and inflation rate are consider as independent variables. This study will use single regressions as a method to understand the relationship between dependent and independent variables.